2022
DOI: 10.1101/2022.09.20.22280154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omicron Subvariants: Clinical, Laboratory, and Cell Culture Characterization

Abstract: Background The variant of concern, Omicron, has become the sole circulating SARS-CoV-2 variant for the past several months. Omicron subvariants BA.1, BA.2, BA.3, BA.4, and BA.5 evolved over the time, with BA.1 causing the largest wave of infections globally in December 2021- January 2022. In this study, we compare the clinical outcomes in patients infected with different Omicron subvariants and compare the relative viral loads, and recovery of infectious virus from upper respiratory specimens. Methods SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Previous studies found that the recovery of infectious virus from cell culture inversely correlated with the presence of SARS-CoV-2 specific IgG in the respiratory tract, specific for both prior VOCs or monovalent vaccines [19] . Moreover, recovery of infectious virus was more frequent from samples with lower mean Ct values, regardless of the subvariant whereas, when Ct values < 20 were considered, BA.5 showed a statistically higher recovery rate of infectious virus compared with other subvariants [20] . In our study, we did not find viable virus on different surfaces, even if a low Ct was obtained from nasal swabs of the enrolled individuals.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies found that the recovery of infectious virus from cell culture inversely correlated with the presence of SARS-CoV-2 specific IgG in the respiratory tract, specific for both prior VOCs or monovalent vaccines [19] . Moreover, recovery of infectious virus was more frequent from samples with lower mean Ct values, regardless of the subvariant whereas, when Ct values < 20 were considered, BA.5 showed a statistically higher recovery rate of infectious virus compared with other subvariants [20] . In our study, we did not find viable virus on different surfaces, even if a low Ct was obtained from nasal swabs of the enrolled individuals.…”
Section: Discussionmentioning
confidence: 84%
“…Third, lightly frequency change of T9I (Class II) and P71L (Class III) mutations may affect the virus pathogenicity particularly among milder Omicron sub-variants (Fig.1 e, right). Compared with Omicron BA.1 and BA.2, the clinical symptoms of BA.4 and BA.5 are more severe 9 . Correspondingly, the frequency of T9I dropped 4.30% and 16.65% in the latter two sub-variants, respectively.…”
Section: Textmentioning
confidence: 92%
“…1 e, right). Compared with Omicron BA.1 and BA.2, the clinical symptoms of BA.4 and BA.5 are more severe 9 . Correspondingly, the frequency of T9I dropped 4.30% and 16.65% in the latter two sub-variants, respectively.…”
Section: Textmentioning
confidence: 92%
See 2 more Smart Citations